Brain-derived neurotrophic factor gene val66met polymorphism and executive functioning in patients with bipolar disorder - Tramontina,Juliana Fernandes (2009)
OBJECTIVE: In the present study, we investigate the association between the val66met polymorphism of the brain-derived neurotrophic factor (BNDF) and the performance on the Wisconsin Card Sorting Test in a sample of Caucasian Brazilian patients with bipolar disorder. METHOD: Sixty-four patients with bipolar disorder were assessed and their performance on the Wisconsin Card Sorting Test was compared with the allele frequency and genotype of the val66met polymorphism of the brain-derived neurotrophic factor. RESULTS: The percentage of non-perseverative errors was significantly higher among patients with the val/val genotype. There was no association between (BNDF) genotype frequency and other Wisconsin Card Sorting Test domains. CONCLUSION: Our results did not replicate previous descriptions of an association between a worse cognitive performance and the presence of the met allele of the val66met brain-derived neurotrophic factor gene polymorphism.